The rank in the nominal sentence of the Kufans (Journal of the College of Basic Education, 2022)
And yet. The subject of rank is one of the topics that preoccupied the minds of former and modern scholars because of its importance in determining the locations of words within the structure. Therefore, we find that they study the subject of rank through the different grammatical chapters through the topics of introduction, delay, deletion, etc. The nominal sentence determines, in light of these patterns, the type of rank, whether it is restricted ranks or free ranks